Telenursing Development of N-SMSI (Short Message Service Intervention) in the care of post-treatment TB patients in hospitals - Renditya Anggana; Filia Sofia Ikasari (Universitas Muhammadiyah Tangerang, 2019)
Tuberculosis (TB) is still a deadly infectious disease in the community. TB patient’s compliance in the consumption of Anti-TB drugs for 6 months, determine the recovery of TB patients. The outpatients TB is most likely to experience a drug dropout which can lead to Multi Drug Resistance Tuberculosis (MDR-TB), so that Supervisors Take Medication are needed to prevent the occurrence of MDR-TB. Ners-Short Message Service Intervention (N-SMSI) is one of the information systems that can developed to prevent the occurrence of MDR-TB. The purpose of writing this article is to describe and analyze the development of N-SMSI telenursing as an information system for conducting observations in the care of TB patients who can help TB patients achieve recovery in a way that effective and efficient. The method in writing this article is the study of literature using a variety of literature related to the application of N-SMSI especially in the prevention of MDR-TB. The results of the literature study show that N-SMSI can be utilized in monitoring patient compliance in consuming OAT, so that expectations cured patients is very large and the mortality rate in TB cases can be suppressed as much as possible. This literature recommends the application of N-SMSI in outpatient TB patients to facilitate activities monitoring by health workers in the prevention of MDR-TB.Keywords: MDR-TB, N-SMS, Telenursing, Tuberculosis